Edukasi Pengenalan dan Pembelajaran Jurnalistik Olahraga pada Mahasiswa Prodi Penjas melalui kunjungan ke Media Harian Fajar dan Media Rakyat News Makassar - aminuddin nyampo; Agus Ismail; Awaluddin; Kurnia Rusli; Ferawati (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2023)
The world of journalism has progressed very rapidly. Along with the changes and the development of the times, journalistic activities also experience a very dynamic process which is marked by the emergence of internet media. Not only that, the branch of journalism also changed, including the birth of sports journalism. Print mass media must adapt to these changes and developments. They are no longer just focusing on the print edition, but have started working on the online version of the media. The focus of journalistic learning is learning outcomes. So as to provide student experience in achieving careers other than being a Physical education teacher. The Physical Education Study Program is one of the study programs that has a journalistic curriculum, especially related to sports journalism so that students are able to hone their talents, interests and abilities to become journalists. The 65 students who were given experience related to sports journalism, immediately visited the Editors of Fajar Daily and Rakyat News. The outputs obtained from this service are (1) establishing partner collaboration with Fajar Daily Editors and Rakyat News to support sports journalism lectures. (2) improvement of sports journalism course syllabus. (3) Direct experience for students as journalists